Sharks in the shallows : attacks on the Carolina coast - Creswell, W. Clay (University of South Carolina Press, 2021)
"The earliest account of a Carolina-based sneak attack was reported on June 24, 1817. On that day, an elderly man named Jemmy was swimming out to his boat which had set adrift off James Island, in Charleston Harbor. Just as he had reached the boat, a large shark struck him with enough force to have supposedly sliced him in two. The shark disappeared, along with the unfortunate fisherman, who was never seen again." Enter the water on the Carolina coast and you are likely less than 100 feet from a shark. Fifty-six of the world's 500 shark species call the Carolinas home for a least a portion of the year. From the foot-long broadband lantern shark, to the great white and massive whale shark, they are drawn by same warm waters that attract tens of millions of human visitors annually. But while numbers of reported shark attacks in the Carolinas are among the highest in the world, they remain exceedingly rare: in 2019, there were eighteen ocean drownings in North and South Carolina, and only one serious and five minor injuries from shark bites. In Sharks in the Shallows, Clay Creswell, a shark bite investigator who covers North and South Carolina for the Global Shark Attack File, shares cases from the file, with reported incidents going back more than 200 years. An engaging, but non-sensational, introduction to the world of shark attacks, it covers the history of shark-human interactions in the Carolinas; shark activity in the Carolinas; profiles of the three species most likely to be involved in attacks, great white, tiger, and bull sharks, as well as others implicated in attacks; and recommendations for safe ocean use. The book also includes as complete listing of all recorded shark attacks in the region. Original black and white illustrations bring the magnificent oceandwellers to life"--